Professional Development: Enhancing Adaptability for a Future-Ready Workforce - Young-Babb, Tonia; Hall, Leslie F.; Kuhn, Annemarie; Pryor, Cristina (International Journal of Advanced Corporate Learning (iJAC), 2025)
As organizations strive to navigate the complexities of a globalized workforce, professional development plays a crucial role in future-proofing operations. This study examines the challenges and opportunities associated with language proficiency, focusing on Native English Speakers (NES) and English as a Second Language (ESL) professionals. By identifying disparities in the design, delivery, and assimilation of training programs, the research explores how language proficiency can serve as both a barrier and facilitator to professional growth. The study highlights the need for inclusive development strategies that address linguistic and cultural challenges while fostering adaptability within organizations. Key stakeholders, including leadership, human resources, educational institutions, and technology providers, are essential in creating a collaborative framework that ensures equal growth opportunities. The ultimate goal is to uncover best practices that promote innovation, inclusivity, and long-term organizational success by integrating diverse talent pools and enhancing training outcomes across a multilingual workforce. Through this strategic approach, organizations can cultivate leadership and agility to thrive in an evolving global market.